Protective Effect of Laminaria japonica with Probiotics on Murine Colitis - Ko, Seok-Jae (Hindawi Publishing Corporation, 2014)
Inflammatory bowel disease (IBD) is a chronically relapsing inflammatory disorder of the gastrointestinal tract. Most IBD treatments are unsatisfactory; therefore, various dietary supplements have emerged as promising interventions. Laminaria japonica (LJ) is an edible seaweed used to regulate digestive symptoms. Probiotics have been reported to improve digestive problems and their simultaneous administration with seaweeds has been shown to produce synergistic therapeutic effects. Here, we investigated the effect of LJ combination with probiotics on dextran sodium sulfate-induced colitis model in mice. Aqueous LJ extracts (LJE) at doses from 100 to 300 mg/kg and probiotics at a dose of 300 mg/kg were orally administered for 7 days. Body weight, colon length, histological score, macroscopic damage, and the levels of cytokines IFN-γ, IL-1β, IL-6, IL-10, IL-12 (P40), IL-12 (P70), IL-17, and TNF-α were assessed. LJE alone caused a significant improvement of colitis signs such as colon length, histological score, and IL-1β and IL-6 production. LJE and probiotics demonstrated a synergistic effect by the histological score and levels of IL-1β, IL-6, and IL-12 (P40) but not IFN-γ, IL-10, and IL-12 (P70). In conclusion, LJE was effective in inducing protection against colitis in mice and acted synergistically with probiotics.